Meeting the Protein Requirements of Broiler Chickens through Plant Sources (Journal of Science and Technology, 2016)
A six-week feeding trial was conducted to determine whether a combination of groundnut cake (GC), soyabean meal (SBM) and brewer’s dried yeast (BDY) can efficiently replace fishmeal in broiler diets. One hundred and eighty (180) 2-week old AF Bosbek commercial strain of broiler chickens were allotted to three dietary treatments in a completely randomized design. The dietary treatments were designated as T1 (containing 180 g fishmeal kg -1 and 50 g each of GC, SBM and BDY.) T2 (containing 90 g fishmeal kg -1 and 50 g each of GC, SBM and BDY kg-1) and T3 (containing 100g each of GC, SBM and BDY kg-1 with no fishmeal). The experimental diets were formulated to be isonitrogenous and isoenergetic. Birds had free access to food and water throughout the study.Replacement of fishmeal with the plant protein supplements, significantly decreased (P – 0.05) body weight gain and feed conversion efficiency but not feed consumption, carcass dressing percentage, percentage blood and feathers. The dietary treatments had significant impact on the moisture, crude protein and ether extract (fat) levels of the meat.Feed cost kg as well as cost of feed to produce a kg liveweight reduced considerably as the levels of SBM, GC and BDY in the diets increased. Health-related problems or mortalities attributable to dietary treatments were not observed.